The reaction of share prices to share buyback in Singapore. - Chang, Shui Lin. (2008)
Our study focuses on SGX-listed firms. Past research has shown signaling to be the most prevalent rationale for a buyback. Thus, the main objective of this project is to analyse the use of share buyback as a signaling tool and its impact. Event study methodolgy was adopted.